2008
DOI: 10.1161/circep.107.691931
|View full text |Cite
|
Sign up to set email alerts
|

Fever Accentuates Transmural Dispersion of Repolarization and Facilitates Development of Early Afterdepolarizations and Torsade de Pointes Under Long-QT Conditions

Abstract: Background-The arrhythmogenic effects of hyperthermia have been highlighted in the Brugada syndrome but remain largely unexplored in other arrhythmic syndromes. The present study examines the effect of hyperthermia on transmural dispersion of action potential duration (TD-APD), early afterdepolarization (EAD) activity, and torsade de pointes (TdP) under long-QT conditions. Methods and Results-Standard and floating glass microelectrodes were used to record action potentials from epicardial, M cell, and endocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…However, the fever induced QT interval prolongation has been reported in patients with type 2 but not in patients with type 1 LQTS. Furthermore, an experimental study using a perfusion wedge model of type 1 LQTS showed that hyperthermia abbreviated the action potential duration of the left ventricular myocardium (9). Therefore; other unknown factors might be associated with the further QT interval prolongation in this patient.…”
Section: Discussionmentioning
confidence: 84%
“…However, the fever induced QT interval prolongation has been reported in patients with type 2 but not in patients with type 1 LQTS. Furthermore, an experimental study using a perfusion wedge model of type 1 LQTS showed that hyperthermia abbreviated the action potential duration of the left ventricular myocardium (9). Therefore; other unknown factors might be associated with the further QT interval prolongation in this patient.…”
Section: Discussionmentioning
confidence: 84%
“…ECGs were centrally read by an external laboratory (eResearch Technology, Inc., Philadelphia, PA, USA). Baseline ECG data were collected in triplicate on day 1 at 0 (pre-dose), 2, 4, 6, 8, 12, 16, 20 and 24 h (after placebo infusion) and on day 8 at 0 (predose), 2,4,6,8,12,16,20,24,30,36 and 48 h (after custirsen infusion). Pre-dose ECGs were collected after dexamethasone administration (in the premedication group) and before custirsen or placebo infusion.…”
Section: Holter Ecg Monitoringmentioning
confidence: 99%
“…Samples were collected within 15 min prior to the start of custirsen infusion and at 2,4,6,8,12,16,20,24,30,36 and 48 h after the start of infusion to match Holter ECG data collection, and on day 15 follow-up. PK parameters (area under the plasma concentration vs. …”
Section: Pharmacokinetics/pharmacodynamicsmentioning
confidence: 99%
“…99,104 The link between hyperthermia and arrhythmias is complex, and there is evidence that elevated temperature increases the transmural dispersion gradient of repolarization, precipitating arrhythmias. 100 While there are no specific LQT3 Na V 1.5 mutations identified which display enhanced temperature sensitivities, biophysical analysis close to physiological temperature is recommended for characterization of these mutations in vivo.…”
Section: Erythromelalgiamentioning
confidence: 99%